Pengaruh Induksi Cathepsin K terhadap Pembetukan Imunoglobulin (IgG) Anti-Cathepsin K, Osteosit, dan Kadar Alkaline Phosphatase (ALP) pada Tikus Putih (Rattus norvegicus L. Betina Galur Wistar Pascaovariektomi - Fransisco Wahyu Santoso; Arif Ismail; Oktavia Rahayu Adianingsih; Yurike Mandrasari (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2012)
ABSTRACT Osteoporosis is a "silent disease" that can weaken bones and cause fractures. Two from five of Indonesia's population at risk of osteoporosis and it is estimated in 2025 that number will become tripled. It has been found a kind of drug, that serves as cathepsin K inhibitors, that shows great potential in reducing osteoporosis. Cathepsin K has an important role in tissue destruction, bone remodeling, and cartilage destruction, This study is aimed to verify the effect of the cathepsin K vaccine candidate to the decrease of bone resorption in Rattusnorvegicus strain wistar post-ovariectomy. Female Rattusnorvegicas Strain Wistar (age: 10-12 weeks) are divided into 5 groups: control (-), control (+) with ovariectomy, the treatment groups are ovariectomized and given cathepsin K 50 ng/200 µL, 100 ng/200 µL, and 200 ng/200 µL.. Surgery perform on the 30th day and then IgG titers of anti-cathepsin K and ALP serum level are measured and the number of osteocytes is counted. ANOVA test shows that the administration of the vaccine candidate, cathepsin K that are added with CFA-IFA, is significantly increase the titers of IgG anti-cathepsin K in the serum (p = 0.00). The administration of cathepsin K 50 ng/200 µL, 100 ng /200 µL, and 200 ng/200 µL do not significantly reduce the number of osteocytes. The administration of cathepsin K 50 ng/200 µL, 100 rig / 200 µL, and 200 ng/200 µL do not increase the ALP serum levels (p> 0.05) significantly. The conclusion of the study is that the administration of the cathepsin K vaccine candidate can increase the IgG anti-cathepsin K titers in Female Rattusnorvegicus Strain Wistar Rats Post-ovariectomy, but do not significantly affect the number of osteocytes and ALP serum levels. Therefore, the osteoporosis vaccine candidate with cathepsin K as a basic material still need to be researched and develop